Pathogenesis of Molar Hypomineralisation: Aged Albumin Demarcates Chalky Regions of Hypomineralised Enamel - Perez, Vidal A.; Mangum, Jonathan E.; Hubbard, Michael J. (Frontiers in Physiology, 2020)
Molar Hypomineralisation (MH) is becoming globally recognised as a significant public health problem linked to childhood tooth decay. However, with causation and pathogenesis unclear after 100 years of investigation, better pathological understanding is needed if MH is to become preventable. Our studies have implicated serum albumin in an extracellular pathomechanism for chalky enamel, opposing longheld dogma about systemic injury to enamel-forming cells. Hypothesising that chalky enamel arises through developmental exposure to serum albumin, this study used biochemical approaches to characterise demarcated opacities from 6-year molars. Addressing contradictory literature, normal enamel was found to completely lack albumin subject to removal of surface contamination. Querying surface permeability, intact opacities were found to lack salivary amylase, indicating that 'enamel albumin' had become entrapped before tooth eruption. Thirdly, comparative profiling of chalky and hard-white enamel supported a dose-response relationship between albumin and clinical hardness of opacities. Moreover, albumin abundance delineated chalky enamel from white transitional enamel at opacity borders. Finally, addressing the corollary that enamel albumin had been entrapped for several years, clear signs of molecular ageing (oxidative aggregation, fragmentation) were identified. By establishing aged albumin as a biomarker for chalky enamel, these findings hold methodological, clinical and aetiological significance. Foremost, direct inhibition of enamel-crystal growth by albumin (here termed 'mineralisation poisoning') at last provides a cogent explanation for the clinical presentation of demarcated opacities. Together, these findings justify pursuit of an extracellular paradigm for the pathogenesis of MH and offer exciting new prospects for alleviating childhood tooth decay through medical prevention of MH.